New data on distribution of Phoenicurusia transcaucasicus (Miller, 1923) (Lepidoptera, Lycaenidae) with description of a new subspecies from Iran - Krupitsky, Anatoly V.; Naderi, Alireza; Hagen, Wolfgang Ten; Lukhtanov, Vladimir A.; Nazari, Vazrick (Zootaxa, 2024)
Distribution of Phoenicurusia transcaucasicus (Miller, 1923) in Iran and neighbouring territories is clarified based on analysis of DNA barcodes, the male genitalia and wing pattern of adults. Our study revealed the widespread distribution of Ph. transcaucasicus throughout northern, northeastern and central Iran. Based on integrative analysis, a new subspecies, Ph. transcaucasicus flamma ssp. n., is described from the Zagros Mountains, the Central Iranian Range and the Alborz Mountains. Compared to the nominotypical subspecies, the new subspecies differs in well-developed orange pattern both of dorsal and ventral sides of the wings, shape of the valva in the male genitalia and distinct COI haplotypes. Additionally, distinct phylogenetic lineage of Ph. transcaucasicus is reported from Kerman Province. Diagnostic characters of the species of Ph. phoenicurus (Lederer, 1870) group of Iran are illustrated.